Between Compliance and Commitment: A Temporal Critical Discourse Analysis of How National and International Oil Companies Respond to Evolving Climate-Related ESG Regulations in Their Public Disclosures, 2016–2026 - Nugroho Nugroho; Rahmatul Husni (Jurnal Locus Penelitian dan Pengabdian, 2026)
Over the decade from the Paris Agreement to the EU Omnibus I deregulation, the regulatory landscape for corporate climate disclosure has shifted from voluntary frameworks toward mandatory reporting, before partially reversing. Yet how National Oil Companies (NOCs) and International Oil Companies (IOCs) have responded to these evolving demands remains underexplored. This research employed longitudinal hybrid Critical Discourse Analysis and thematic content analysis on 176 reports from sixteen NOCs and IOCs across four regions (2016–2026 Q1). Guided by regulatory-response theory, legitimacy theory, and institutional logics, it examines how NOC and IOC disclosures diverged or converged in response to successive regulatory regimes and what discursive strategies were employed. Findings reveal three key patterns. First, European IOCs rapidly adopted TCFD/ISSB frameworks, with "net-zero" rhetoric increasing 340%, while NOCs showed only 120% increase. Second, following Omnibus I, European IOCs immediately reduced Scope 3 details and removed sectoral ESRS references, confirming that regulatory pressure drives symbolic compliance rather than substantive commitment. Third, the talk-walk gap persists across all companies, with average low-carbon capital expenditure at 18% for IOCs and only 4% for NOCs. NOCs in the Middle East exhibited the widest gap between rhetoric and investment action. This research fills a clear gap: no peer-reviewed qualitative study has conducted a temporal NOC-versus-IOC comparison across multiple regions spanning the full Paris-to-Omnibus-I arc. The findings contribute to corporate sustainability disclosure, energy governance, and ESG regulation literatures, with implications for policymakers and investors evaluating the credibility of oil and gas companies' energy-transition commitments.